2019
DOI: 10.21077/ijf.2019.66.2.86920-14
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern and its correlation to the presence of tdh gene and CRISPR-Cas system in Vibrio parahaemolyticus strains isolated from seafood

Abstract: Vibrio parahaemolyticus is a pathogen native to the aquatic environment. In this study, 46 environmental V. parahaemolyticus isolates were subjected to a correlational analysis to find the association between their antimicrobial susceptibility pattern, prevalence of CRISPR-Cas system and thermostable direct hemolysin (tdh) gene. Antibiotic resistance profiling against eleven antibiotics revealed the isolates to be multidrug resistant. Isolates exhibited highest resistance to vancomycin (97.8%) followed by ampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…The result of this study corroborates earlier findings; however, we could detect CRISPR in two of the tdh− trh + and one of the tdh− trh− isolates. The presence of CRISPR in the tdh− isolates were also reported in a previous study [41]. The CRISPR loci detected in this study is located on the V. parahaemolyticus island-7 (VPAI-7) region of chromosome 2, which encodes the tdh gene and are closely associated with tdh+ V. parahaemolyticus [43][44][45], thus this may be the reason why this CRISPR loci is more prevalent in the tdh+ isolates.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The result of this study corroborates earlier findings; however, we could detect CRISPR in two of the tdh− trh + and one of the tdh− trh− isolates. The presence of CRISPR in the tdh− isolates were also reported in a previous study [41]. The CRISPR loci detected in this study is located on the V. parahaemolyticus island-7 (VPAI-7) region of chromosome 2, which encodes the tdh gene and are closely associated with tdh+ V. parahaemolyticus [43][44][45], thus this may be the reason why this CRISPR loci is more prevalent in the tdh+ isolates.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, nearly half of the V. parahaemolyticus isolates had an MAR index ≥ 0.2, which indicated that these isolates originated from high-risk sources that have been exposed to antibiotics, such as humans and aquaculture, and seafood might be considered as a possible vehicle for pathogen transmission. Previous studies have reported that the V. parahaemolyticus isolates from seafood showed an MAR index > 0.2 [41,42]. Thus, antimicrobial resistance should continue to be monitored to ensure seafood safety.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with other studies elsewhere that detected an MAR index above 0.2 among 45% of pandemic and non-pandemic V. parahaemolyticus isolated from seafood [69]. The MAR indices that exceed 0.2 indicated that these isolates originated from high-risk contamination and may pose human risks [70,71].…”
Section: Discussionsupporting
confidence: 92%